A pilot study investigating the effect of extended contact lens wear on limbal and central corneal morphology. Issue 1 (February 2022) - Ye, Xiangyu; Kang, Pauline; Peguda, Rajini; Chau, Sylvia; Chen, Melissa; Golebiowski, Blanka; Carnt, Nicole
Abstract: Purpose: To investigate the effect of long-term extended soft contact lens wear on limbal and central corneal cell morphology, and limbal architecture. Methods: Each participant attended a study visit involving in vivo confocal microscopy of central corneal and limbal epithelium. Scans were graded by five masked graders for three features: central epithelial irregularity, limbal epithelial irregularity and the prominence of palisades of Vogt. The variability of grades between different graders and the difference of grades between extended wearers and daily soft/non-contact lens wearers were assessed. Results: Nineteen participants (9 extended soft contact lens wearers and 10 daily soft/non-contact lens wearers) aged 31–65 years were enrolled in this study. Scans from 37 eyes were included in the analysis. Agreement between graders for each feature was moderate to good with inter class correlation >0.7. While there were no significant differences in central epithelial cell irregularity ( p = 0.527) and the prominence of palisade of Vogt ( p = 0.182) between extended or daily soft/non-contact lens wearers, limbal epithelial cell irregularity showed a trend with increased irregularity in extended soft contact lens wearers ( p = 0.091). Conclusions: While no differences in limbal cell morphology and structure or central epithelial cell was found in this subjective grading study of extended wearers compared to daily soft/non-contact lens wearers, further studies using a larger sample size or a longitudinal study design are warranted.